2010
DOI: 10.1098/rsbl.2010.0640
|View full text |Cite
|
Sign up to set email alerts
|

Uneven distribution of cryptic diversity among higher taxa of parasitic worms

Abstract: Cryptic species cause problems for estimates of biodiversity. In the case of parasites, cryptic species also plague efforts to detect potential zoonotic diseases or invasive pathogens. It is crucial to determine whether the likelihood of finding cryptic species differs among higher parasite taxa, to better calibrate estimates of diversity and monitor diseases. Using published reports of cryptic species of helminth parasites identified using molecular tools, I show that the number of species found is strongly r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
70
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(73 citation statements)
references
References 17 publications
(10 reference statements)
2
70
0
Order By: Relevance
“…This suggests an uneven distribution of cryptic diversity among higher taxa. A few years ago, Poulin (2011) reported a similar uneven distribution among higher groups of parasitic helminths. Specifically, after correcting for sampling effort (i.e.…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations
“…This suggests an uneven distribution of cryptic diversity among higher taxa. A few years ago, Poulin (2011) reported a similar uneven distribution among higher groups of parasitic helminths. Specifically, after correcting for sampling effort (i.e.…”
Section: Introductionmentioning
confidence: 92%
“…A few years ago, Poulin (2011) reported that more cryptic species were uncovered among trematodes than other helminth groups when controlling for the number of DNA sequences obtained per study. Here, using a much larger dataset, we generally confirmed this earlier finding.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Unrecognised diversity is routinely encountered in molecular surveys of digeneans (Poulin, 2011) and some lag can be expected between the genetic detection and identification, description or characterisation of putative species with other methods. Furthermore, provisional species delineations can be valuable.…”
Section: Introductionmentioning
confidence: 99%